(untitled) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2025)
Cijawura Bandung 1930an. This research uses the historical method with the following research steps: heuristics (collecting primary and secondary data), criticism (external and internal), interpretation (interpreting the data that has been obtained), and finally historiography (writing history). This research aims to find out the life history and activities of KHR Muhamad Burhan and the activities he carried out in the development of Islamic Boarding Schools and Islam in Cijawura village. Based on the results of the research, it was revealed that KHR Muhamad Burhan was born to KHR Muhamad Qoernaen and Hj. Nyi Mas Asiah. Nyi Mas Asiah in the village of Keresek Cibatu Garut, at the age of 15 he began his education in various Islamic boarding schools in West Java such as Bayongbong, Sukamiskin, Sempur, Gentur. The learning experience from the boarding school she had traveled made her get ideas in creating works in the form of writing. His existence in Cijawura cannot be separated from the support of a community leader named Abah Haji Syukur, who later married his daughter, Hj. Kaltsum. Kaltsum. His activities in building the ummah were realized through an Islamic boarding school founded in 1930 under the name Pondok Pesantren Cijawura Margasari.